Pergulatan Paham Negara Kesejahteraan (Welfare State) dan Negara Regulasi (Regulatory State) dalam Perkara Konstitusional - Bisariyadi Bisariyadi (Fakultas Hukum Universitas Islam Indonesia, 2016)
The concept of Welfare State principally can be applied along with the Regulation State. Welfare refers to the dream of a nation and here carrying out the function of regulatory is a means to achieve it. The alignment of these two concepts is possible. The issue concerned in this study is a debate in the decisions of the Constitutional Court regarding the application to understand the Welfare State and Obligation State in Constitution. The issue is focused on the economic affairs and social welfare, especially in the formation of bodies that have power in ruling as stated in Article 33 and Article 34 of the 1945 Constitution. The issue of this research is regarding the Constitutional Court ruling to dissolve the Executive Agency for Oil and Gas but on the other hand there is the Constitutional Court decision confirming the existence of Social Security Agency. In fact, both are the legal entities established by the state to perform the control and regulation. This research used normative-juridical method and concluded that the Constitution insists on applying the concept of the Welfare State, but it does not mean that there is no space for the development of the concept of Regulation State. Today, granting a ruling authority to certain bodies is inevitable in order to lighten the State burden.